ANALISIS STATIK BRACKET ROLL BRUSH MESIN TENSOR MENGGUNAKAN METODE FEA - Yunnanta Adi Putra; M. Nushron Ali Mukhtar (ELEMEN : JURNAL TEKNIK MESIN, 2023)
This research uses the finite element analysis method to examine the design and safety analysis of the bracket roll brush. The problem occurs when the bracket roll brush is deformed during the wetting process, which impacts the printout of the product, where the ink dirt is still attached. The bracket roll brush uses 6061 T6 aluminum material of 38 mm x 25 mm x 19 mm, and the weight generated from mass properties is ± 0.03 Kg. The loading variable on the bracket roll brush is 147 N, 172 N, and 196 N. The simulation results show that the bracket roll brush has a maximum stress value of 85.551 N/mm2, and the value at the maximum stress of the bracket roll brush is still below the material yield strength value of 275,000 N/mm2. The simulation results on the bracket roll brush have a maximum displacement value of 0.0035 mm. And the simulation results on the bracket roll brush have a minimum safety factor value of 3.214.